PENGEMBANGAN LEMBAR KERJA SISWA MODEL INKUIRI TERBIMBING MATERI ELEKTROKIMIA KELAS XII SMA - Eka Tina Nur Ula Tuqa; Suyono Suyono; Bambang Sugiarto (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
This research aimed to develop valid, practical, and effective worksheet to support electrochemistry learning using guided inquiry model. Development  of  worksheet based on ADDIE model (Analyse, Design, Develop, Implement, and Evaluate). Worksheet were implemented at grade XII chemistry students using one group pretest-posttest design. Validity of worksheet was measured from relevance and consistency based on expert judgment with minimum score of 2,6. Practicality of worksheet was measured from students activity with minimun percentage of 60%. Effectivenes of worksheet was measured from its impact to increase students cognitive achievement significanly. Validity and practicality was analyzed using descriptive statistics, whereas effectiveness of cognitive achievement was analyzed using inferential t-test. The result of data analysis were: (1) content validiy and construct validity of worksheet developed was very valid; (2) students activity were very good; (3) cognitive achievement has increased significanly both in pilot implementation and final implementation